Consumer preferences and marketing strategy for black pule (Alstonia spectabilis) antimalarial tablet prototypes in South Central Timor - Novia Maulina; Sari Dewi Setyowati; Salma Rizqika Irwanadi; Hajar Sugihantoro; Riza Ambar Sari; Ziyana Walidah; Maximus M. Taek; Burhan Ma’arif (International Journal of Public Health Science (IJPHS), 2026)
Malaria remains endemic in eastern Indonesia, and resistance to conventional antimalarial drugs necessitates alternative treatments. Black pule (Alstonia spectabilis) is one of the plants that has been researched and claimed to be a natural ingredient that can treat malaria. Black pule prototype has been prepared for the downstream stage through commercialization. Before that, it is necessary to conduct marketing research to ensure the success of the marketing. Therefore, this study evaluates consumer preferences and formulates marketing strategies for black pule antimalarial tablets. This study involved 100 respondents selected using cluster and purposive sampling across three malaria-endemic sub-districts in South Central Timor Regency. Using a quantitative-descriptive approach, data were collected through questionnaires and analyzed with descriptive statistics. The results show that most consumer targets stated that the antimalarial tablet prototype of black pule has a good impression and characteristics. Approximately 69-77% of respondents rated the product positively across shape, color, taste, aroma, size, and overall organoleptic attributes. The results indicate that the majority of respondents gave positive evaluations and expressed a preference for the product’s shape, color, taste, aroma, size, and overall organoleptic characteristics. Findings support aggressive marketing strategies for herbal antimalarial tablets in endemic regions. Based on these findings, an aggressive S-O marketing strategy is recommended, emphasizing product promotion, participation in health-related expos, strengthened digital outreach, and concise educational initiatives to improve public acceptance of the herbal antimalarial tablet.